The toxic effects of s(+)-ketamine on differentiating neurons in vitro as a consequence of suppressed neuronal Ca2+ oscillations. - Sinner, Barbara; Friedrich, Oliver; Zink, Wolfgang; Zausig, York; Graf, Bernhard (Anesthesia and analgesia, 2011)
BACKGROUND In the immature brain, neuronal Ca2+ oscillations are present during a time period of high plasticity and regulate neuronal differentiation and synaptogenesis. In this study we examined the long-term blockade of hippocampal Ca2+ oscillations, the role of the N-methyl-D-aspartate (NMDA) receptors and the effects of S(+)-ketamine on neuronal synapsin expression. METHODS Hippocampal neurons were incubated at day 15 in culture with the specific NMDA receptor antagonists dizocilpine (MK 801, 100 μM) or S(+)-ketamine (3 μM to 25 μM) for 24 hours. Terminal-deoxynucleotidyl-transferase (TUNEL) and activated caspase3 were used to detect apoptotic neurons. Ca2+ oscillations were detected after loading the neurons with the Ca2+-sensitive dye fura-2AM, and dual wavelength excitation fluorescence microscopy was performed. Ca2+/calmodulin kinase II (CaMKII) was measured using Western blots. Synapsin was identified with confocal antisynapsin immunofluorescence. RESULTS Blocking the NMDA receptor with MK 801 or 25 μM S(+)-ketamine resulted in a significant increase in apoptotic neurons. MK 801 led to a significant increase in cytosolic Ca2+ concentration and reduction of the amplitude and frequency of the Ca2+ oscillations. Similar to MK 801, the long-term application of S(+)-ketamine resulted in a significant increase in cytosolic Ca2+ concentration 24 hours after washout. This was associated with a down-regulation of the CaMKII and a reduction of the synapsin 24 hours after washout. CONCLUSION Neuronal Ca2+ oscillations mediate neuronal differentiation and synaptogenesis via activating CaMKII. By acting via the NMDA receptor, S(+)-ketamine exerts its toxic effect through the suppression of neuronal Ca2+ oscillations, down-regulation of the CaMKII, and consecutively reduced synaptic integrity.